How Environmental Concern, Warm Glow, and Financial Impact Decision of Adopting Solar PV - Hana Azalia; Hanna Isrania; Nabila Indrasari; Bachtiar H. Simamora (Bina Nusantara University, 2021)
The research objective was to determine the significant impact of the environment concern, warm glow, and financial benefits towards Indonesia Power’s consumers motivation in using solar PV. The data was taken by questionnaire, with a sample size of 91 respondents, all consumers are solar PV users in Jawa Timur. The analysis was conducted by using SPSS with a single and multiple regression analysis method. The result indicates that the environmental concern, warm glow, and financial benefits have significant impact towards the motivation in adopting solar PV in Indonesia. Thus, the results can help Indonesia Power to foster and promote renewable Energy specifically solar PV. Furthermore, the research can help solar PV producers in how they can better promote their products.